1992
DOI: 10.1111/j.1432-1033.1992.tb17411.x
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric measurements of thermal denaturation of stefins A and B

Abstract: Thermal denaturation of two homologous proteins, low-M, cysteine-proteinase inhibitors stefins A and B, has been investigated by microcalorimetry. Calorimetric enthalpies, as well as the temperatures at maximum heat capacity, were determined as a function of pH for each protein. Transitions were found reversible at all pH values examined (5.0, 6.5, 8.1) for the thermally more stable stefin A, in contrast to stefin B. Stefin B shows a sharp irreversible transition around 65°C at pH 6.5 and 8.1, probably due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…11,12 SteA shows remarkable thermal stability with a reversible transition observed at 90.8 8C and folding enthalpy of 490 kJ/mol, 16 all suggesting that a SteA-based scaffold would meet criteria (2) and (3). Thus, our preliminary study and the published literature suggested that SteA was a strong candidate for the development of a new scaffold.…”
Section: Resultsmentioning
confidence: 56%
“…11,12 SteA shows remarkable thermal stability with a reversible transition observed at 90.8 8C and folding enthalpy of 490 kJ/mol, 16 all suggesting that a SteA-based scaffold would meet criteria (2) and (3). Thus, our preliminary study and the published literature suggested that SteA was a strong candidate for the development of a new scaffold.…”
Section: Resultsmentioning
confidence: 56%
“…Heat capacity differences (&C,) were not determined directly from the thermograms owing to baseline uncertainties. The heat capacity difference on unfolding, obtained from the slope of the calorimetric enthalpy against temperature, was 7.95 kJ K ' mol-' (not shown) which is significantly higher than 6.28 kJ K-' mol-' measured previously [35], or the calculated value of 5.69 kJ K-' mol-' 1451. The slope could be corrected to 5.86 if the fractions of the native and native-like states from CD data were taken into account.…”
Section: Microcalorimetric Measurements Lowsult Concentrationmentioning
confidence: 87%
“…It was shown, nevertheless, that the active component of the inhibitor was monomeric [34]. Microcalorimetric studies of the two proteins have confirmed that stefin A is much more stable and does not deviate from two-state behavior [35]. Regarding physiological processes, it has been proposed that lower expression of stefin A plays a key role in tumour invasion [36].…”
mentioning
confidence: 99%
“…23 Thermal denaturation of both proteins by differential scanning calorimetry (DSC) reveals a big difference in melting temperatures, 64.9 o C vs. 94.5 o C for stefins B and A at pH 6.5, respectively. 24 Using structural thermodynamics, underlying structural reasons for different thermodynamic behavior were predicted. 25 It was suggested that the difference in accesible hydrophobic surfaces of the two native proteins, in addition to a difference in the number of h-bonds in the ␤ sheet structure, may account for the differences in thermodynamic behavior.…”
Section: Introductionmentioning
confidence: 99%